Heterozygous aggrecan variants are associated with short stature and brachydactyly: Description of 16 probands and a review of the literature - Sentchordi-Montané, L (2018)
OBJECTIVE: Mutations in the aggrecan gene (ACAN) have been identified in two autosomal dominant skeletal dysplasias, spondyloepiphyseal dysplasia, Kimberley type (SEDK), and osteochondritis dissecans, as well as in a severe recessive dysplasia, spondyloepimetaphyseal dysplasia, aggrecan type. Next-generation sequencing (NGS) has aided the identification of heterozygous ACAN mutations in individuals with short stature, minor skeletal defects and mild facial dysmorphisms, some of whom have advanced bone age (BA), poor pubertal spurt and early growth cessation as well as precocious osteoarthritis. DESIGN AND METHODS: This study involves clinical and genetic characterization of 16 probands with heterozygous ACAN variants, 14 with short stature and mild skeletal defects (group 1) and two with SEDK (group 2). Subsequently, we reviewed the literature to determine the frequency of the different clinical characteristics in ACAN-positive individuals. RESULTS: A total of 16 ACAN variants were located throughout the gene, six pathogenic mutations and 10 variants of unknown significance (VUS). Interestingly, brachydactyly was observed in all probands. Probands from group 1 with a pathogenic mutation tended to be shorter, and 60% had an advanced BA compared to 0% in those with a VUS. A higher incidence of coxa valga was observed in individuals with a VUS (37% vs 0%). Nevertheless, other features were present at similar frequencies. CONCLUSIONS: ACAN should be considered as a candidate gene in patients with short stature and minor skeletal defects, particularly those with brachydactyly, and in patients with spondyloepiphyseal dysplasia. It is also important to note that advanced BA and osteoarticular complications are not obligatory conditions for aggrecanopathies/aggrecan-associated dysplasias.